Production of Tissue Inhibitor of Metalloproteinases-1 (TIMP-1) by Human Astrocytic Tumors - ARAI, Yoshikazu; SATO, Kazufumi; KODERA, Toshiaki; NAKAGAWA, Takao; KABUTO, Masanori; KUBOTA, Toshihiko (Neurologia medico-chirurgica, 1995)
Production of tissue inhibitor of metalloproteinases-1 (TIMP-1), a specific inhibitor of matrix metalloproteinases, was investigated in human astrocytic tumors (n = 15) and normal brain tissues (n = 3). Enzyme immunoassay indicated that TIMP-1 levels in the culture media of tumor explants were significantly higher in glioblastomas as compared with anaplastic astrocytomas, astrocytomas, and normal brain tissues. Immunohistochemistry using a monoclonal antibody against TIMP-1 demonstrated that TIMP-1 was detectable mainly in tumor cells, especially in glioblastoma. These results suggest that increased expression of TIMP-1 is associated with the malignant progression of astrocytic tumors.